Pencegahan dan Penanganan Kekerasan Seksual pada Perguruan Tinggi Keagamaan Islam Negeri di Aceh - Idris, M. Arif; Azhari, Azhari; Sulaiman, Muhammad (Seutia Hukamaa Cendekia, 2024)
State Islamic Religious Universities (PTKIN) in Aceh have their own challenges in dealing with sexual violence. The culture and religious values that are upheld in Aceh should be a strong foundation for forming a safe and comfortable environment for all campus residents. However, it needs to be recognized that sexual violence can occur anywhere, including in institutions based on religious values. The purpose of the research is to find out the concrete steps implemented by PTKIN in Aceh in preventing and handling sexual violence in the university environment. The research was conducted using a qualitative method with research locations in 5 PTKIN in Aceh. Data collection was carried out using interview, observation, and documentation techniques on selected research objects and subjects. Data analysis is carried out by carrying out stages of data reduction, data presentation, and conclusion. The results of the study show that the Prevention and Handling of Sexual Violence at PTKIN has been carried out by referring to PMA number 72 of 2022. However, the implementation of the prevention and handling of sexual violence is still not optimal. Only UIN Ar-Raniry is seen to have systematically prevented and prevented sexual violence. UIN Ar-Raniry already has special regulations related to PPKS, there is already a ULT PPKS and has carried out socialization of Prevention and Handling of Sexual Violence programmatically and sustainably .